2021
DOI: 10.1108/ebr-06-2020-0150
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the level of a corporation’s public disclosure of its managerial values and its level of organizational authenticity

Abstract: Purpose This study aims to explore if corporations that publicly disclose more information about their managerial values are also more organizationally authentic in enacting these values. Design/methodology/approach A maturity model of managerial values is used that ordinally ranks a corporation’s level of managerial values enactment using corporate annual reports. The samples of corporations’ corporate reports are qualitatively content analyzed, and the outcomes are statistically tested. Findings The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…sustainability), customer needs, risk mitigation (e.g. pandemic) and policy implementation (Bai et al , 2021; Neher et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…sustainability), customer needs, risk mitigation (e.g. pandemic) and policy implementation (Bai et al , 2021; Neher et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The work of Neher et al (2021) has identified that the more an organization publicly discusses its values in its annual reports, the greater the likelihood that it will enact them. This results in higher maturity levels and greater support from internal and external stakeholders.…”
Section: Living Like You Preachmentioning
confidence: 99%
“…As underpinned by SCT theories, MNCs must further develop PM processes and address digital communication challenges in the emerging VUCA environment in their quest to recover, build and maintain talented employees. COVID-19 and the unexpected need for remote work accelerated the digital transformation of workplaces(Amankwah-Amoah et al, 2021;Nagel, 2020;Peter et al, 2023). At the same time, in organisations, particularly MNCs, internal communication has transformed into digital internal communication (DIC)(Wuersch et al, 2023).…”
mentioning
confidence: 99%